REFLEKSI NASIONALISME TOKOH DALAM FILM WATHANI AL-GHALI: TELAAH RESEPSI SASTRA - Erwhintiana, Ifi; Fitriani, Laily (Arabi : Journal of Arabic Studies, 2021)
This research aims to reveal audiences reflection about propaganda of Palestine Liberation that presented through nationalism value  in film wathani al-ghali based on Stuart Hall Perspective. This research is  decriptive qualitative. The subject of this research are 40 students of Arabic  Languange and Literature in UIN Maulana Malik Ibrahim by purposive sampling based on curent criteria. The results of this research showed that actualization of  nationalism value in film wathani al-ghali are about 18 in various form as  propaganda of Palestine Liberation. Those actualization are blatant uprising,  being killed for Palestine’s defenses, fooling the Israeli army and attacking  them. Audience receptions for the representation nationalism value in the film  interpreted into a reflection of propaganda of Palestine Liberation. Percentage  of audiences are 78% are in dominant hegemony position, 22% are in  negoitation position, and no ocucupies for the opposition. Some underlying  factors are background knowledge that related to Palestinian conflict, simple  flow, and also getting much moral values from the film.